The novel reconfigurable double-layer half-mode SIW filter with tunable DMS structure. Issue 14 (22nd September 2018) - You, Bin; Chen, Linyun; Luo, Guoqing
ABSTRACT: The contribution of this paper is to present a reconfigurable double-layer half-mode substrate integrated waveguide (HMSIW) bandpass filter with continuous center frequency and 3 dB bandwidth (BW) tuning capabilities. The double-layer rectangular HMSIW is subjected to vertical electrical coupling and magnetic coupling through the proposed semicircle aperture and rectangular slot etched on the middle metal layer. Due to this mixed electric and magnetic coupling structure, the 3 dB BW can be tuned and one adjustable transmission zero (TZ1) is introduced. Varactors (CV2) are used to adjust the center frequency. The parasitic passband produced by the higher-order mode TE102 can be suppressed, thanks to the proposed T-shapes defected microstrip structure. Compared with the conventional horizontal coupling SIW filters, the proposed HMSIW filter also shows a compact physical area. To demonstrate the proposed design method, a double-layer HMSIW bandpass filter is fabricated and measured. Both the simulation and measured results show a center frequency tuning range of 1.21–1.72 GHz, as well as demonstrate a 3 dB BW tuning range of 62–101 MHz around 1.21 GHz, 97–213 MHz around 1.45 GHz, 225–310 MHz around 1.72 GHz. The insertion loss ranges from 1.18 to 6.32 dB. Furthermore, simulated and measured results also show a good agreement.